Análise citogenética em espécies de Hypostominae Lacépède, 1803 (Osteichthyes, Loricariidae) da bacia dos rios Uruguai e Paraná : enfoque biogeográfico e filogenético - Silva, Vanessa Bueno da (2014)
Fishes are a wide and diverse group, with many particularities that make it interesting for studying chromosome evolution. Among fishes, Hypostomus is the most specious genus from the subfamily Hypostominae, with considerable intraspecific variation in morphology and color patterns and a high number of species which are not formally described. The great number of species, distributed through most of South America, hinders broad comparative analyses, scenery also observed for cytogenetical, phylogenetical and biogeographical studies on the genus. Even though the number of analyzed species is small compared to the diversity of the genus, studies performed until now show that data obtained from molecular, cytogenetical and biogeographical analyses have been complementing each other, increasing the understanding on the evolution of the group. Regarding cytogenetical analyses, the number of nominal Hypostomus species analyzed is still low. Most analyzed species belong to the Paraná River basin and there are few species belonging to northern basins and none from southern basins where the genus is distributed. Regarding species from Brazil, this would represent mainly species from the Amazonas and Uruguay basins. Since there is great chromosome diversity on the genus, that seems to be related to the distribution of species, the absence of analyses from these regions is an obstacle for undertanding the group. Due to the absence of analyses from potentially important groups in the genus, exitent theories for chromosome evolution in Hypostomus deal with general trends, and there are no analyses of Hypostomus subgroups. Considering the difficulties found in clarifying the evolution of the genus, and that correlations between phylogeny, chromosome evolution and biogeography may help undestanding species differentiation, the present paper aimed to analyze subgroups of closely related Hypostomus species from the Uruguay River. On the first chapter, a bibliographical review is made on the Uruguay River basin and Hypostomus. On the second chapter, three Hypostomus species, H. albopunctatus, H. luteus and H. isbrueckeri, are compared cytogenetically, showing how phylogenetic hypostesis may be correlated with cytogenetics for a better comprehension of complex groups. Since there are species with similar diploid numbers in different clades within Hypostomus, only the diploid number is not enough to separate groups. this research is the first to use the phylogeny of groups within the genus to coordenate the comparison between karyotypes of closely related species. These species are part of the same clade in Hypostomus, which contains all species that occurr only in the Uruguay River basin and some species from Paraná River basin. The results showed great similarity between the chromosome structure of these species, specially H. albopunctatus and H. isbrueckeri. Two species that were once recognized as synonymous, H. luteomaculatus and H. regani, were cytogenetically compared in the third chapter. Both showed the same diploid numbers, chromosome formula and location of the 5S rDNA, being distinguished only by differences on the 18S rDNA sites.this chapter shows the use of cytogenetics in taxonomy, being an important tool for groups that have confusing taxa delimitation. Finally, on chapter four, species from three Hypostominae tribes are analyzed: Rhinelepis aspera, from Rhinelepini, Pterygoplichthys ambrosettii, from Pterigoplichthini and Megalancistrus parananus, from Ancistrini. The correlation of the results with the phylogeny of Hypostominae reveals a diploid number of 52 chromosomes as basal for the tribes Ancistrini and Pterygoplichthini. While most Hypostominae genera show conserved karyotypes, the genera Ancistrus and Hypostomus show divergent chromosome evolution. Considering 2n=54 chromosomes as an ancestral feature for Loricariidae, Rhinelepini shows ancestral diploid numbers. In Hypostominae, the increase of diploid numbers is observed in Hypostomus. Pterygoplichthini shows diploid numbers of 52 chromosomes, with the reduction of one pair compared to the ancestral diploid number. This feature is observed also in many genera from Ancistrini, with the exeption of Ancistrus, that shows a reduction of diploid number. So, Hypostominae as a whole does not show many derived features, since these features are concentrated in genera Hypostomus and Ancistrus.